Predictive Value of the Delta Neutrophil Index for Placenta Accreta in Cases with Placenta Previa - Karanfil Yaman, Fikriye; Dogru, Sukran; Ezveci, Huriye; Akkus, Fatih; Arslan, Emine; Alp, Elifsena Canan; Acar, Ali (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: This study aimed to investigate the predictive value of the Delta Neutrophil Index (DNI) in detecting placenta accreta spectrum (PAS) in patients with placenta previa (PP). STUDY DESIGN: A retrospective study was conducted on 735 patients diagnosed with PP. Demographic characteristics, laboratory results, and maternal and fetal outcomes were obtained from electronic medical records. DNI levels were assessed with other inflammatory markers, and logistic regression analysis was performed to identify predictors of the PAS. Receiver operating characteristic (ROC) analysis was used to determine the diagnostic accuracy of DNI in distinguishing PAS cases from non-PAS cases. RESULTS: Logistic regression analysis revealed that the number of previous cesarean sections and DNI levels were significant predictors of the development of PAS (p=0.07). Elevated DNI levels were independently associated with an increased risk of PAS (p<0.05). The optimal cut-off value of DNI for diagnosing PAS was determined as 0.07 with a sensitivity of 67.5% and a specificity of 56.26%. The area under the ROC curve (AUC) for DNI was calculated as 0.639, indicating moderate diagnostic accuracy. CONCLUSION: This study demonstrates that DNI is a potential predictor of PAS development in cases of PP. Integrating DNI assessment into routine prenatal care protocols in PP patients may facilitate early risk identification and inform clinical management strategies. Further research is needed to confirm these findings and explore the broader applicability of DNI in obstetric practice.